Proton conductor solid oxide battery composite electrode material and application thereof

By preparing composite electrode materials of LCFCN and BZCYYb, the problems of thermal expansion mismatch and conductivity incompatibility of H-SOC cathode materials were solved, achieving high efficiency in electrochemical performance and long-term stability, making them suitable for industrial applications.

CN121282223APending Publication Date: 2026-01-06SHANGHAI BRIGHT-H TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511332518.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-17
Publication Date
2026-01-06

AI Technical Summary

Technical Problem

Existing cathode materials for proton conductor solid oxide batteries (H-SOC) suffer from problems such as thermal expansion mismatch, thermomechanical failure, uncoordinated proton/electron transport, low oxygen reduction activity, and insufficient long-term stability.

Method used

LCFCN material was prepared by sol-gel method using La0.6Ca0.4Fe0.8Co0.1Ni0.1O3-δ (LCFCN) and BaZr0.4Ce0.1Yb0.1O3-δ (BZCYYb) in a mass ratio of 7:3. The high proton conductivity of BZCYYb was combined to form a tightly bonded electrode-electrolyte interface, which optimized thermal matching and conductivity.

Benefits of technology

It significantly improves the structural stability and electrochemical performance of the battery, reduces the activation energy barrier of the oxygen reduction reaction, enhances the long-term stability and power output of the battery, and is low in cost and suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121282223A_ABST
    Figure CN121282223A_ABST
Patent Text Reader

Abstract

The invention discloses a proton conductor solid oxide battery composite electrode material and application, and belongs to the technical field of solid oxide batteries (SOC), the composite electrode material is formed by compounding a La0. 6Ca0. 4Fe0. 8Co0. 1Ni0. 1O3-delta (short for LCFCN) material with a perovskite structure and a BaZr0. 4Ce0. 4Y0. 1Yb0. 1O3-delta (short for BZCYYb) material according to a mass ratio of 7: 3, and the composite electrode material is named as an LCFCN-BZCYYb composite electrode material. Wherein the LCFCN is prepared by adopting a sol-gel method, the particle size of the LCFCN is concentrated at 350-450 nm, the average thermal expansion coefficient of the LCFCN is 13.4 * 10 <-6 > / K, and the LCFCN is excellently matched with a BZCYYb electrolyte; and meanwhile, the LCFCN has an electron-oxygen ion-proton triple conduction characteristic. The composite electrode material is used as an H-SOC cathode and is matched with a BZCYYb electrolyte and a NiO anode to form a battery, the maximum output power density of the battery can reach 1.13 W / cm < 2 > at the working temperature of 700 DEG C, the ohmic impedance is as low as 0.11 ohm cm < 2 >, the problems that existing cobalt-based, strontium-based and nickel-based cathode materials are mismatched in thermal expansion, high in impedance, poor in stability and the like are effectively solved, and the service life of the battery is prolonged. And the electrochemical performance and the long-term operation reliability of the H-SOC are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid oxide cell (SOC) technology, specifically relating to the design and application technology of electrode materials for proton-conducting solid oxide cells (H-SOC), and particularly to a composite electrode material for proton-conducting solid oxide cells and its application. Background Technology

[0002] Solid oxide batteries (SOCs), as highly efficient electro-chemical energy conversion devices, combine power generation and hydrogen production functions, achieving an energy conversion efficiency exceeding 60% (up to 80% when coupled with waste heat utilization). To reduce the cost and stability issues associated with the high temperatures of traditional oxygen-ion-conducting SOCs (O-SOCs) at 800℃-1000℃, proton-conducting SOCs (H-SOCs), with their mid-to-low temperature operating range of 500℃-700℃, have become a research hotspot. They utilize proton-conducting electrolytes (such as BaZrO3-based and BaCeO3-based materials), avoiding the high costs of high-temperature alloy interconnects while reducing the risk of material corrosion and interface failure. However, the core bottleneck in improving the performance of H-SOCs lies in the cathode material: while cobalt-based cathodes (such as BSCF) exhibit high catalytic activity, their thermal expansion coefficient (15×10⁻⁶) is limited. -6 / K-18×10 -6 / K) and electrolytes (such as BZCYYb, 10.1×10 -6 The SrCO3 / K mismatch is severe and easily leads to interfacial delamination; Strontium-based cathodes (such as LSCF) have a slightly better coefficient of thermal expansion, but they easily react with CO2 to form a SrCO3 insulating layer, resulting in a sharp increase in impedance; although nickel-based cathodes have better thermal matching, they suffer from insufficient proton conduction (<1×10⁻⁶). -4 The activity of S / cm (S / cm) and chromium poisoning issues decreased by more than 30% within 100 hours.

[0003] To overcome these challenges, researchers attempted to optimize cathode performance through composite structures or elemental doping, but these efforts all led to new problems: while combining cobalt-based materials with electrolytes reduced the coefficient of thermal expansion, it also caused the electronic conductivity to drop from 100 S / cm to below 50 S / cm; although dual-element doped LaFeO3-based perovskites improved oxygen reduction activity, they still faced insufficient proton conduction (<5 × 10⁻⁶). - 4The stability of Ce dissolution under high humidity conditions and the S / cm (S / cm) problem are also issues. Although perovskite materials (ABO3 type) are potential candidates due to their tunable structure and conductivity, traditional single / dual element doping systems suffer from a "triple conductivity imbalance" defect—insufficient proton mobility restricts low- and medium-temperature activity, the oxygen reduction activation barrier is too high (>1.0 eV) limiting power output, and high doping levels can easily lead to the precipitation of impurity phases that damage the structure. More importantly, existing perovskite cathodes lack microstructure adaptability in the H-SOC architecture, the proton / electron transport and gas phase diffusion channels are not coordinated, the reaction sites are limited to narrow three-phase interfaces, and thermomechanical mismatch will accumulate stress and cause microcracks during long-term operation, ultimately leading to performance degradation.

[0004] Existing H-SOC cathode materials have not yet achieved synergistic optimization of "thermal matching-conductivity-catalysis-stability", and there is an urgent need to develop new composite cathode materials to overcome technical bottlenecks. Summary of the Invention

[0005] In view of the above-mentioned defects in the prior art, the technical problem to be solved by the present invention is that existing proton conductor solid oxide battery (H-SOC) cathode materials generally face multiple technical dilemmas such as "poor thermal matching, triple conductivity imbalance, low oxygen reduction catalytic activity, and insufficient long-term stability".

[0006] The purpose of this invention is to provide an integrated solution of "materials-preparation-application-device" to address the technical bottlenecks of existing H-SOC cathode materials.

[0007] To achieve the above objectives, the present invention provides a proton conductor solid oxide battery composite electrode material, which is composed of perovskite La 0.6 Ca 0.4 Fe 0.8 Co 0.1 Ni 0.1 O 3-δ Materials (LCFCN) and BaZr 0.4 Ce 0.1 Yb 0.1 O 3-δ The material (abbreviated as BZCYYb) is composited at a mass ratio of 7:3, and the composite electrode material is named LCFCN-BZCYYb composite electrode material. The crystal structure of LCFCN is a pure phase perovskite structure, free of impurity phases such as La2O3, CaO, Fe2O3, Co3O4, and NiO. The BZCYYb is a commercially available high-purity proton conduction material with a purity ≥99.99%.

[0008] Preferably, the La 0.6 Ca 0.4 Fe 0.8 Co 0.1 Ni 0.1O 3-δ The material was prepared using the sol-gel method, and the specific steps included:

[0009] Step 1: Press La 0.6 Ca 0.4 Fe 0.8 Co 0.1 Ni 0.1 O 3-δ According to the stoichiometric ratio, weigh 15.3g of La(NO3)3·6H2O, 3.6g of Ca(NO3)2·4H2O, 16.1g of Fe(NO3)3·9H2O, 1.5g of Co(NO3)2·6H2O, 1.5g of Ni(NO3)2·6H2O, 28.9g of citric acid, and 29.4g of EDTA.

[0010] Step 2: Dissolve the nitrate in 200 mL of deionized water, and stir at 300 r / min for 30 min in a 40°C constant temperature water bath until completely dissolved;

[0011] Step 3: Add the citric acid and EDTA to the solution obtained in Step 2, and continue stirring for 60 minutes until completely dissolved. Adjust the pH of the solution to 7-8 using 25%-28% ammonia.

[0012] Step 4: Place the solution obtained in Step 3 in a 90℃ oil bath and stir at a rate of 200r / min for 10h to evaporate the water and form a wine-red transparent sol.

[0013] Step 5: Dry the sol in an oven at 200°C for 12 hours to obtain a solid precursor;

[0014] Step 6: Place the solid precursor in a muffle furnace and calcine it according to the procedure of "room temperature → 600℃ (3℃ / min, hold for 60min) → 800℃ (2℃ / min, hold for 300min) → 400℃ (3℃ / min, cool to room temperature with the furnace)". After grinding, LCFCN powder is obtained.

[0015] The present invention also provides a method for preparing the aforementioned proton conductor solid oxide battery composite electrode material, comprising the following steps:

[0016] Step A: Weigh LCFCN powder and BZCYYb powder in a mass ratio of 7:3, wherein the LCFCN powder is prepared by the aforementioned method and the purity of the BZCYYb powder is ≥99.99%;

[0017] Step B: Add the LCFCN powder and BZCYYb powder to a grinding device and mix and grind them at room temperature to obtain a uniform mixed powder;

[0018] Step C: Place the mixed powder in an 80°C oven and dry for 2 hours to remove the moisture adsorbed during the grinding process, thus obtaining the LCFCN-BZCYYb composite electrode material.

[0019] Preferably, the grinding equipment in step B is an agate mortar or a planetary ball mill; if an agate mortar is used, the grinding rate is 30 r / min for manual grinding and the grinding time is 60 min; if a planetary ball mill is used, the grinding media is zirconia balls, the ball-to-material ratio is 5:1, the rotation speed is 300 r / min, and the grinding time is 120 min; no additional additives are used during the grinding process to avoid introducing impurities.

[0020] This invention also provides an application of the aforementioned proton conductor solid oxide battery composite electrode material in the preparation of proton conductor solid oxide batteries. The LCFCN-BZCYYb composite electrode material is used as the cathode active material of the proton conductor solid oxide battery, and together with the electrolyte and anode, it forms a complete battery structure to achieve efficient electrochemical conversion of fuels such as hydrogen.

[0021] Preferably, the structure of the proton conductor solid oxide battery, from top to bottom, consists of an anode layer, an electrolyte layer, and a cathode layer; wherein, the anode layer is a NiO-BZCYYb anode support (NiO to BZCYYb mass ratio 6:4) and a NiO anode, the electrolyte layer is a BZCYYb dense layer, and the cathode layer is the LCFCN-BZCYYb composite electrode material layer.

[0022] Preferably, the cathode layer is prepared by a slurry coating method, specifically including:

[0023] Step a: Weigh LCFCN-BZCYYb composite electrode material and binder at a mass ratio of 100:40, wherein the binder is ethyl cellulose terpineol solution, and the mass ratio of ethyl cellulose to terpineol is 1:10;

[0024] Step b: Add the composite electrode material and binder to an agate mortar and grind for 60 minutes to form a uniform cathode slurry without particle agglomeration. The viscosity of the slurry is controlled at 5000 mPa·s-8000 mPa·s.

[0025] Step c: Apply the cathode paste to the upper surface of the electrolyte layer using a brushing method, with a coating area of ​​2.5-3.5 cm². 2 A wet cathode layer is obtained.

[0026] Preferably, step c further includes a drying and calcination process for the cathode layer: the electrolyte coated with the wet cathode layer is placed in an 80°C forced-air oven to dry for 2 hours to remove the terpineol solvent; then the temperature is raised to 120°C and dried for 1 hour to remove residual moisture; finally, it is placed in a muffle furnace and calcined at 950°C for 2 hours, with a heating rate of 5°C / min and a cooling rate of 5°C / min, so that the cathode layer and the electrolyte layer form a tightly bonded interface without cracks or peeling.

[0027] This invention also provides a proton conductor solid oxide battery, comprising an anode assembly, an electrolyte assembly, and a cathode assembly; the anode assembly includes a NiO-BZCYYb anode support (NiO to BZCYYb mass ratio 6:4), a NiO anode, and an anode current collector; the electrolyte assembly is a BZCYYb dense electrolyte sheet; the cathode assembly includes the LCFCN-BZCYYb composite electrode material and a cathode current collector; the anode assembly, electrolyte assembly, and cathode assembly are interfacially bonded through high-temperature co-firing, and the overall battery sealing is ensured by a glass sealing ring.

[0028] Preferably, the battery operates under the following conditions: operating temperature 500℃-700℃; fuel gas is introduced into the anode side, which is pure hydrogen or a hydrogen-nitrogen mixture (hydrogen integral ≥ 50%), with a gas flow rate of 40mL / min-60mL / min; air is introduced into the cathode side, with a gas flow rate of 100mL / min-120mL / min; during battery operation, the external circuit load resistance between the anode and cathode is 0.1Ω-10Ω, and the battery can operate stably for more than 1000 hours with a performance degradation rate ≤ 5%.

[0029] Compared with the prior art, the beneficial technical effects of the present invention are as follows:

[0030] (1) This invention effectively solves the thermal expansion mismatch problem of existing proton conductor solid oxide battery (H-SOC) cathode materials, significantly improving the structural stability of the battery. This invention uses the sol-gel method to prepare La... 0.6 Ca 0.4 Fe 0.8 Co 0.1 Ni 0.1 O 3-δ (LCFCN) perovskite material with a low coefficient of thermal expansion of 13.4 × 10⁻⁶. -6 / K, with BaZr 0.4 Ce 0.4 Y 0.1 Yb 0.1 O 3-δ The coefficient of thermal expansion of the (BZCYYb) electrolyte is 10.1 × 10⁻⁶. -6 The difference between / K and is only 3.3 × 10. -6 / K, which is much smaller than that of existing cobalt-based cathodes (difference > 5 × 10⁻⁶). -6 / K) and strontium-based cathode (difference > 2 × 10) -6 / K). By compounding LCFCN and BZCYYb at a mass ratio of 7:3, the thermal matching is further optimized, and a tightly bonded electrode-electrolyte interface can be constructed. This avoids interface delamination during high-temperature calcination in battery preparation and long-term thermal cycling, fundamentally solving the structural failure problem of existing cathodes caused by thermomechanical mismatch.

[0031] (2) This invention achieves synergistic optimization of the triple conductivity characteristics of electrons, oxygen ions, and protons, significantly improving the electrochemical performance of the battery. LCFCN material itself possesses excellent triple conductivity, and when combined with BZCYYb, the composite electrode material retains both the high electronic conductivity (approximately 110 S / cm at 700℃) and oxygen ion conductivity of LCFCN, while also leveraging the high proton conductivity characteristics of BZCYYb (proton conductivity ≥ 5 × 10⁻⁶ at 700℃). -2 This composite electrode material (S / cm) forms a highly efficient carrier transport network. This synergistic effect expands the battery reaction sites from the traditional narrow three-phase interface to the entire cathode interface, significantly reducing the activation barrier for the oxygen reduction reaction. In actual testing, the H-SOC using this composite electrode material as the cathode achieved a maximum output power density of 1.13 W / cm² at an operating temperature of 700°C. 2 The ohmic impedance is only 0.13Ωcm 2 It is far superior to existing cobalt-based and nickel-based cathode cells (whose maximum power density is generally <0.8W / cm³). 2 Ohmic impedance > 0.2Ωcm 2 ).

[0032] (3) The composite electrode material of this invention possesses excellent long-term stability and environmental adaptability, solving the defects of poor corrosion resistance and rapid performance degradation of existing materials. On the one hand, the LCFCN material effectively suppresses the precipitation of Sr elements through the synergistic doping of Fe, Co, and Ni elements, avoiding the risk of SrCO3 insulating layer formation in CO2 atmosphere of existing strontium-based materials; on the other hand, the introduction of BZCYYb component not only improves proton conduction but also protects LCFCN from the leaching of Ce elements under high humidity environment, while inhibiting the reaction between Ni elements and Cr ions released from interconnect materials, avoiding the "chromium poisoning" problem. It has been verified that H-SOC based on this composite electrode material operates stably for more than 1000h at 700℃ with a performance degradation rate of ≤5%, which is far lower than that of existing nickel-based cathode batteries (degradation of more than 30% in 100h) and cobalt-based cathode batteries (degradation of more than 15% in 500h), providing a guarantee for the long-term reliable operation of the battery.

[0033] (4) This invention has the advantages of low cost and industrial application, facilitating large-scale production and promotion. During the preparation process, LCFCN uses the sol-gel method, with raw materials being inexpensive analytical reagents such as conventional nitrates and citric acid, eliminating the need for expensive rare metals. Subsequent processing of the composite electrode material only requires mature processes such as grinding and slurry coating, without the need for special equipment such as pulsed laser deposition or sputtering, resulting in low equipment investment costs. Preparation parameters (such as calcination temperature, grinding time, and coating process) can be directly adapted to industrial production lines, easily achieving batch yields of kilograms or more. Compared to existing high-end cathode materials that rely on complex processes, this invention has significant advantages in cost control and production efficiency, laying the foundation for the industrialization of H-SOC.

[0034] The following will further explain the concept, specific structure, and technical effects of the present invention in conjunction with the accompanying drawings, so as to fully understand the purpose, features, and effects of the present invention. Attached Figure Description

[0035] Figure 1 This is a particle size distribution diagram of LCFCN perovskite material;

[0036] The figure shows a unimodal particle size distribution with no obvious multi-peak or large particle agglomeration peaks; D10 = 350 nm, D50 = 400 nm, D90 = 450 nm, and Span = (D90 - D10) / D50 = 0.2, indicating that the material has a uniform particle size, meeting the requirements for nanoscale electrode materials, and can effectively expand the active sites on the electrode surface (specific surface area up to 15 m²). 2 / g);

[0037] Figure 2 The thermal expansion curve of LCFCN perovskite material;

[0038] The figure shows that the thermal expansion curve exhibits a linear relationship within the range of 25℃-800℃, and the slope of the fitted straight line is the average coefficient of thermal expansion (13.4×10). -6 / K); The curve deviates from linearity above 800℃, which is caused by the ordering of oxygen vacancies in the perovskite lattice. Therefore, the working temperature of the battery in this invention is controlled below 700℃ to avoid sudden changes in the coefficient of thermal expansion.

[0039] Figure 3 The full-cell impedance diagram of the LCFCN-BZCYYb composite cathode;

[0040] In the diagram: The Nyquist plot consists of two semicircles. The high-frequency semicircle (1kHz-1MHz) corresponds to the ohmic impedance (RΩ) between the electrolyte and the electrode, and the low-frequency semicircle (1Hz-1kHz) corresponds to the electrode polarization impedance (Rp). At 700℃, RΩ = 0.11Ωcm 2 Rp = 0.08Ωcm 2 The total impedance Rtotal = 0.19 Ωcm2 At 550℃, RΩ=0.27Ωcm 2 Rp = 0.35Ωcm 2 The total impedance Rtotal = 0.62 Ωcm 2 This indicates that increasing the temperature can significantly reduce the battery impedance, which is consistent with the performance characteristics of H-SOC at medium and low temperatures.

[0041] Figure 4 Full-cell IVP curves for the LCFCN-BZCYYb composite cathode;

[0042] In the figure: the IV curve shows an approximately linear decrease, indicating relatively small battery polarization; the IP curve first rises linearly and then flattens out, with the peak value representing the maximum output power density; at 700℃, the maximum power density is 1.13 W / cm³. 2 (Current density = 2.5 A·cm) -2 (Voltage = 0.45V); 0.78W / cm² at 650℃ 2 =0.47W / cm² at 600℃ 2 =0.34W / cm² at 550℃ 2 All of these performance metrics are superior to those of existing H-SOCs of the same type. Detailed Implementation

[0043] The following description, with reference to the accompanying drawings, illustrates several preferred embodiments of the present invention to make its technical content clearer and easier to understand. The present invention can be embodied in many different forms, and the scope of protection of the present invention is not limited to the embodiments mentioned herein.

[0044] In the accompanying drawings, components with the same structure are indicated by the same numerical designation, and components with similar structures or functions are indicated by similar numerical designations. The dimensions and thicknesses of each component shown in the drawings are arbitrary, and the present invention does not limit the dimensions and thicknesses of each component. To make the illustrations clearer, the thickness of some components has been appropriately exaggerated in the drawings.

[0045] Example 1: Preparation of LCFCN material

[0046] 1. Raw material preparation

[0047] Press La 0.6 Ca 0.4 Fe 0.8 Co 0.1 Ni 0.1 O 3-δ According to the stoichiometric ratio, accurately weigh the following raw materials (accuracy 0.01g):

[0048] La(NO3)3·6H2O: 15.30g (purity 99.9%);

[0049] Ca(NO3)2·4H2O: 3.60g (purity 99.5%);

[0050] Fe(NO3)3·9H2O: 16.10g (purity 99.9%);

[0051] Co(NO3)2·6H2O: 1.50g (purity 99.9%);

[0052] Ni(NO3)2·6H2O: 1.50g (purity 99.9%);

[0053] Citric acid (C6H8O7): 28.90g (purity 99.5%);

[0054] EDTA(C 10 H 16 N2O8): 29.40g (purity 99.5%);

[0055] Ammonia water (NH3·H2O): 25%-28%;

[0056] Deionized water: 200 mL (resistivity ≥ 18.2 MΩ·cm).

[0057] 2. Sol preparation

[0058] 2.1 Add the above nitrates sequentially to a 500mL three-necked flask, add 200mL of deionized water, place the three-necked flask in a 40℃ constant temperature water bath, turn on the magnetic stirrer, stir at a speed of 300r / min for 30min, until the nitrates are completely dissolved and a light yellow-green transparent solution is formed (without visible particles).

[0059] 2.2 While stirring, slowly add citric acid and EDTA powder, and continue stirring for 60 minutes. During this time, the solution color will gradually turn into a light yellow transparent liquid without any precipitate forming (if a precipitate forms, add a small amount of deionized water and extend the stirring time).

[0060] 2.3 Install a separatory funnel and slowly drip ammonia into the solution at a rate of 1 mL / min, while monitoring the pH value in real time with a pH meter. When the pH value reaches 7.5 (intermediate value to ensure stability), stop adding ammonia. At this point, the solution will turn into a wine-red transparent liquid with a slight increase in viscosity.

[0061] 2.4 Transfer the three-necked flask to a 90℃ constant temperature oil bath, adjust the stirring speed to 200 r / min, and stir continuously for 10 h; observe the state of the solution every 2 h to ensure no stratification or precipitation; after 10 h, the water in the solution will have evaporated completely, forming a wine-red viscous sol (the sol does not flow when the flask is inverted).

[0062] 3. Gel drying

[0063] The wine-red sol was transferred to a 5L glass beaker and placed in an electrically heated constant-temperature drying oven at 200℃ for 12 hours. During the drying process, the sol gradually solidified into a loose solid (gel) in the first 6 hours, and residual moisture was removed in the last 6 hours. After drying, a fluffy solid precursor was obtained, which was black in color.

[0064] 4. Calcination synthesis

[0065] 4.1 Take out the dried solid precursor, crush it into small pieces with a particle size of <5mm, put it into a 50mL corundum crucible (purity 99%), and put the crucible into a box-type muffle furnace.

[0066] 4.2 Setting the muffle furnace heating program:

[0067] Room temperature (25℃) → 600℃: heating rate 3℃ / min, time (600-25) / 3≈191.7min;

[0068] Heating at 600℃ for 60 minutes, during which the organic matter in the gel (citric acid, EDTA, nitrate decomposition products) is burned and decomposed, producing gases such as CO2, H2O, and NO2, which are discharged through the muffle furnace exhaust port;

[0069] 600℃→800℃: Heating rate 2℃ / min, time taken (800-600) / 2=200min;

[0070] Hold at 800℃ for 300 minutes to ensure that metal ions react fully to form the perovskite crystal phase;

[0071] 800℃→400℃: Cooling rate 3℃ / min, time taken (800-400) / 3≈133.3min;

[0072] 400℃ → Room temperature: Cooling with the furnace takes about 240 minutes (to 25℃).

[0073] 4.3 After the muffle furnace has cooled to room temperature, remove the corundum crucible and transfer the calcined product (black block) to an agate mortar. Grind manually for 30 minutes to obtain black powdered LCFCN material with a particle size distribution of 350nm-450nm (measured by a laser particle size analyzer).

[0074] 5. Characterization of LCFCN materials

[0075] 5.1 Particle size analysis: A laser particle size analyzer was used, with ethanol as the test medium, and ultrasonic dispersion for 10 min (power 300W); Figure 1As shown, the results indicate a particle size distribution of D10 = 350 nm, D50 = 400 nm, D90 = 450 nm, and Span = 0.2, demonstrating excellent particle size uniformity and effectively improving the electrode's specific surface area (BET test result: 15.2 μm). 2 / g).

[0076] 5.2 Thermal expansion coefficient test: A thermal expansion meter was used in air atmosphere, with a heating rate of 5℃ / min, and a test temperature range of 25℃-800℃; the results are as follows. Figure 2 As shown, the average coefficient of thermal expansion is 13.4 × 10⁻⁶. -6 / K, with BZCYYb electrolyte (10.1×10 -6 The difference between / K) is 3.3 × 10 -6 / K, which meets the thermal matching requirements.

[0077] Example 2: Preparation of LCFCN-BZCYYb composite electrode material

[0078] 1. Raw material preparation

[0079] LCFCN powder: prepared in Example 1, black powder, particle size 400 nm, purity ≥99.5%;

[0080] BZCYYb powder: commercially available, purity 99.99%, particle size 500nm;

[0081] Agate mortar: 10cm in diameter, 99.9% purity;

[0082] Planetary ball mill.

[0083] 2. Mixed grinding (comparing the two types of equipment)

[0084] 2.1 Option A (Agate Mortar):

[0085] Weigh 7.00g of LCFCN powder and 3.00g of BZCYYb powder (mass ratio 7:3) and put them into an agate mortar;

[0086] Grind manually at a rate of approximately 30 rpm for 60 minutes; scrape the powder off the mortar wall every 10 minutes to ensure even mixing.

[0087] After grinding, the powder is black and uniform, with no visible white BZCYYb agglomerates.

[0088] 2.2 Option B (Planetary Ball Mill):

[0089] Weigh 7.00 g of LCFCN powder and 3.00 g of BZCYYb powder and place them in a 50 mL zirconia ball mill jar;

[0090] Add zirconia balls (5mm in diameter) at a ball-to-material ratio of 5:1 (by mass) and seal the mill jar.

[0091] Set the ball mill parameters as follows: rotation speed 300 R / min, grinding time 120 min, forward and reverse rotation interval 5 min;

[0092] After grinding, the powder was taken out. There was no obvious agglomeration, and the particle size distribution D50 = 420nm (tested by laser particle size analyzer).

[0093] 3. Drying treatment

[0094] The mixed powder obtained from either scheme A or scheme B was transferred to a ceramic petri dish and placed in an 80℃ forced-air drying oven (model DHG-9075A) for 2 hours to obtain the composite electrode material. The drying process removed moisture adsorbed during grinding to prevent agglomeration during subsequent slurry preparation. After drying, the powder mass showed no significant change (mass loss <0.1%), indicating that the moisture had been completely removed.

[0095] Example 3: Preparation of a proton conductor solid oxide battery

[0096] In this embodiment, the LCFCN-BZCYYb composite electrode material prepared in Example 2 is used as the cathode active material of the proton conductor solid oxide battery. Together with the electrolyte and anode, it forms a complete battery structure to achieve efficient electrochemical conversion of fuels such as hydrogen.

[0097] The structure of the proton conductor solid oxide battery, from top to bottom, consists of an anode layer, an electrolyte layer, and a cathode layer. The anode assembly includes a NiO-BZCYYb anode support (NiO to BZCYYb mass ratio 6:4), a NiO anode, and an anode current collector. The electrolyte layer is a dense BZCYYb layer. The cathode assembly includes the LCFCN-BZCYYb composite electrode material and a cathode current collector.

[0098] The cathode layer is prepared by a slurry coating method, specifically including:

[0099] Step a: Weigh LCFCN-BZCYYb composite electrode material and binder at a mass ratio of 100:40. The binder is an ethyl cellulose terpineol solution, wherein the mass ratio of ethyl cellulose to terpineol is 1:10.

[0100] Step b: Add the composite electrode material and binder to an agate mortar and grind for 60 minutes to form a uniform cathode slurry without particle agglomeration. The viscosity of the slurry is controlled at 5000 mPa·s-8000 mPa·s.

[0101] Step c: Apply the cathode paste to the upper surface of the electrolyte layer using a brushing method, with a coating area of ​​1-2 cm². 2A wet cathode layer is obtained.

[0102] Step c is followed by a drying and calcination process for the cathode layer: the electrolyte coated with the wet cathode layer is dried in an 80°C oven for 2 hours to remove the terpineol solvent; then the temperature is raised to 120°C and dried for 1 hour to remove residual moisture; finally, it is placed in a muffle furnace and calcined at 950°C for 2 hours, with a heating rate of 5°C / min and a cooling rate of 5°C / min, to form a tightly bonded interface between the cathode layer and the electrolyte layer, without cracks or peeling. Platinum paste is brushed onto both electrodes after calcination, and after the platinum paste dries completely, a proton-conducting solid oxide battery is obtained.

[0103] The battery operates under the following conditions: operating temperature 500℃-700℃; fuel gas is introduced into the anode side, which is pure hydrogen or a hydrogen-nitrogen mixture (hydrogen integral ≥ 50%), with a gas flow rate of 40mL / min-60mL / min; air is introduced into the cathode side, with a gas flow rate of 100mL / min-120mL / min; during battery operation, the external circuit load resistance between the anode and cathode is 0.1Ω-10Ω, and the battery can operate stably for more than 1000 hours with a performance degradation rate ≤ 5%.

[0104] Air was introduced at a rate of 100 mL / min to the cathode side of the solid oxide battery prepared in Example 1, and hydrogen was used as the fuel gas at a rate of 40 mL / min. The impedance and maximum power density at these temperatures were recorded at 700 °C, 650 °C, 600 °C, and 550 °C, respectively. The results are as follows: Figure 3 , Figure 4 As shown. By Figure 3 It can be seen that the ohmic impedance of the solid oxide cell using LCFCN-BZCYYb composite material as the cathode can reach 0.11, 0.17, 0.20, and 0.27 Ωcm² at 700℃, 650℃, 600℃, and 550℃, respectively. Figure 4 It can be seen that the maximum power density at 700℃, 650℃, 600℃, and 550℃ can reach 1.13, 0.78, 0.47, and 0.34 W / cm2, respectively. Figure 3 In the Nyquist plot, two semicircles are used. The high-frequency semicircle (1 kHz - 1 MHz) corresponds to the ohmic impedance (RΩ) between the electrolyte and the electrode, and the low-frequency semicircle (1 Hz - 1 kHz) corresponds to the electrode polarization impedance (Rp). At 700 °C, RΩ = 0.11 Ωcm. 2 Rp = 0.08Ωcm 2 The total impedance Rtotal = 0.19 Ωcm 2 At 550℃, RΩ=0.27Ωcm 2 Rp = 0.35Ωcm 2The total impedance Rtotal = 0.62 Ωcm 2 This indicates that increasing the temperature can significantly reduce the battery impedance, which is consistent with the performance characteristics of H-SOC at medium and low temperatures. Figure 4 In the middle section: the IV curve shows an approximately linear decrease, indicating relatively small battery polarization; the IP curve first rises linearly and then flattens out, with the peak value representing the maximum output power density; at 700℃, the maximum power density is 1.13 W / cm³. 2 (Current density = 2.5 A·cm) -2 (Voltage = 0.45V); 0.78W / cm² at 650℃ 2 =0.47W / cm² at 600℃ 2 =0.34W / cm² at 550℃ 2 All of these performance metrics are superior to those of existing H-SOCs of the same type.

[0105] The preferred embodiments of the present invention have been described in detail above. It should be understood that those skilled in the art can make numerous modifications and variations based on the concept of the present invention without creative effort. Therefore, all technical solutions that can be obtained by those skilled in the art based on the concept of the present invention through logical analysis, reasoning, or limited experimentation on the basis of existing technology should be within the scope of protection defined by the claims.

Claims

1. A proton-conductor solid-oxide cell composite electrode material, characterized in that, La 0.6 Ca 0.4 Fe 0.8 Co 0.1 Ni 0.1 O3δ materials and BaZr 0.4 Ce 0.1 Yb 0.1 The composite electrode material is named as LCFCN-BZCYYb composite electrode material.

2. The proton conductor solid oxide cell composite electrode material according to claim 1, characterized in that, The La o.6 Ca 0.4 Fe 0.8 Co 0.1 Ni 0.1 The O3δ material is prepared by a sol-gel method, and the specific steps include: Step 1 : 0.5 g of La(NO3)3-6H2O, 0.5 g of Ca(NO3)2-4H2O, 0.5 g of Fe(NO3)3-9H2O, 0.5 g of Co(NO3)2-6H2O, 0.5 g of Ni(NO3)2-6H2O were weighed out in stoichiometric ratio of La : Ca : Fe : Co : Ni = 1 : 1 : 1 : 1 :

1. 0.6 Ca 0.4 Fe 0.8 Co 0.1 Ni 0.1 O 3-δ Step 1 : 0.5 g of La(NO3)3-6H2O, 0.5 g of Ca(NO3)2-4H2O, 0.5 g of Fe(NO3)3-9H2O, 0.5 g of Co Step 2: The nitrate salt is sequentially dissolved in deionized water, and stirred in a constant temperature water bath until completely dissolved; Step 3: Citric acid and EDTA are added to the solution obtained in step 2, and continue to stir until completely dissolved, and adjust the pH of the solution to 7-8 with ammonia water; Step 4: The solution obtained in step 3 is placed in an oil bath, and the water is evaporated to form a transparent sol of wine red color; Step 5: The sol is dried in an oven to obtain a solid precursor; Step 6: The solid precursor is calcined in a muffle furnace, and after grinding, LCFCN powder is obtained.

3. A method of producing a proton-conductor solid-oxide cell composite electrode material as claimed in claim 1, characterized by, The following steps are included: Step A: LCFCN powder and BZCYYb powder with a mass ratio of 7:3 are weighed respectively; Step B: The LCFCN powder and BZCYYb powder are added to a grinding device and mixed and ground at room temperature to obtain a uniform mixed powder; Step C: The mixed powder is dried in an oven to remove the water adsorbed during the grinding process, thereby obtaining the LCFCN-BZCYYb composite electrode material.

4. The production method according to claim 3, characterized by, The grinding device in step B is an agate mortar or a planetary ball mill.

5. Use of a proton-conductor solid oxide cell composite electrode material as claimed in claim 1 for the production of a proton-conductor solid oxide cell, characterized in that, The LCFCN-BZCYYb composite electrode material is used as the cathode active material of the proton conductor solid oxide cell, and the electrolyte and anode are combined to form a complete cell structure, realizing efficient electrochemical conversion of hydrogen and other fuels.

6. Use according to claim 5, characterized in that, The structure of the proton conductor solid oxide cell from top to bottom is an anode layer, an electrolyte layer, and a cathode layer; wherein the anode layer includes a NiO-BZCYYb anode support and a NiO anode, the electrolyte layer is a BZCYYb dense layer, and the cathode layer is the LCFCN-BZCYYb composite electrode material layer.

7. Use according to claim 6, characterized in that, The cathode layer is prepared by a slurry coating method, specifically including: Step a: LCFCN-BZCYYb composite electrode material and a binder are weighed according to a mass ratio of 100:40, and the binder is an ethyl cellulose and terpineol solution with a mass ratio of 1:10; Step b: The composite electrode material and the binder are added to a mortar and ground to form a uniform and non-particle agglomerated cathode slurry; Step c: The cathode slurry is coated on the upper surface of the electrolyte layer by brushing to obtain a wet cathode layer.

8. Use according to claim 7, characterized in that, After step c, the cathode layer also includes a drying and calcining process: the electrolyte coated with the wet cathode layer is dried in an oven to remove the terpineol solvent; then it is heated and dried to remove residual moisture; finally, it is calcined in a muffle furnace to form a tightly bonded interface between the cathode layer and the electrolyte layer.

9. A proton-conductor solid oxide cell, characterized by, The cell includes an anode assembly, an electrolyte assembly, and a cathode assembly; the anode assembly includes a NiO-BZCYYb anode support, a NiO anode, and an anode current collector; the electrolyte assembly is a BZCYYb dense electrolyte sheet; the cathode assembly includes LCFCN-BZCYYb composite electrode material and a cathode current collector; the anode assembly, electrolyte assembly, and cathode assembly are combined by high-temperature co-firing to realize interface bonding.

10. The proton-conductor solid oxide cell according to claim 9, characterized in that, The working conditions of the cell are: working temperature 500-700℃; fuel gas is introduced on the anode side, and the fuel gas is pure hydrogen or hydrogen-nitrogen mixed gas; air is introduced on the cathode side.